Practicing Genre-Based Language Teaching Model to Improve Students’ Achievement of Writing Skills - Haerazi Haerazi; Lalu Ari Irawan (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
This study investigated the use of genre-based language teaching model in the teaching of writing skills to improve students’ low achievement. It was aimed at improving the achievement of the fifth semester of English language education study program. This study was classroom action research. The subjects were the 4th semester in academic year 2017/2018. The procedure of the study included two steps namely the preliminary study and the action. The preliminary study collected information dealing with the students’ problems and the action presented the steps of the classroom action research. The data were collected through observation, questionnaire, and testing. The data were analyzed quantitatively and qualitatively. The result of the study showed that the genre-based language teaching model can improve the students’ writing achievement. Before the action, the average score of students’ writing achievement was 55 and the average score after the action was 76. The result was higher than the subject minimum passing grade which is 75. The improvement was supported by two indicators. First, students felt easy to write a descriptive text because the teaching steps guided them to practice writing much more according to the generic structures of the text. Last but not least, students felt compatible with the topics asked to be written because they have background knowledge of those.